2013
DOI: 10.1177/0193945913483881
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent-Friendly Remedies for the Challenges of Focus Group Research

Abstract: Focus groups are an increasingly popular method of qualitative research; however, as with any research method, limitations emerge that were not anticipated. This article reviewed the limitations reported in 21 research studies, published between 2002 and 2012, to identify the common concerns of researchers in focus group studies with adolescents. Limitations focused on methodological concerns, recruitment challenges, and the potential influences of peers and the moderator on research results. Remedies are sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Not only can the gender of the group participants influence the responses of the focus group participants but so can the gender of the focus group moderator. Depending on the study topic, a moderator with the same gender as the group members in single-gender groups can be advantageous (Daley, 2013;Yager, Diedrichs, & Drummond, 2013).…”
Section: Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only can the gender of the group participants influence the responses of the focus group participants but so can the gender of the focus group moderator. Depending on the study topic, a moderator with the same gender as the group members in single-gender groups can be advantageous (Daley, 2013;Yager, Diedrichs, & Drummond, 2013).…”
Section: Settingmentioning
confidence: 99%
“…Using icebreakers can make it easier for children to start the discussion (Coyne & Carter, 2018;Coyne, Hayes, & Gallagher, 2009;Daley, 2013;Fielden et al, 2011;Greene & Hogan, 2005;Griffiths et al, 2014;McGarry, 2015;Moffat et al, 2009). This may involve something simple, such as making and wearing their own name badges, drawing pictures, or listening to themselves speak on tape.…”
Section: Introduction and Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…During recruitment, a member of the research team should explain the study and its benefits, address questions or concerns, and obtain contact information through the use of a sign-up sheet for those interested in private follow-up. Further, providing details about the study, with consent forms,may help facilitate conversations with parents/guardians and improve participation (Daley, 2013). Providing details about the study alongside consent forms, has been shown to facilitate conversations with parents/guardians prior to a study and to improve participation and retention rates (Berry et al, 2013).…”
Section: Additional Recommendations For Successful Collaborations Witmentioning
confidence: 99%
“…Moreover, the interviews were conducted in focus groups in an adolescent population. In this population there is a risk that their peers influenced their responses (Daley 2013). Therefore, the findings from the study must be treated with some caution.…”
Section: Limitationsmentioning
confidence: 92%